Highly active photocatalytic asphalt pavement for NOx removal using iron-doped g-C3N4. Issue 11 (2nd November 2022) - Shan, Bailin; Cao, Xuejuan; Yang, Xiaoyu; Shang, Ting; Ding, Yongjie; Tang, Boming
Abstract : Low degradation efficiency limited the application of photocatalytic material in pavement construction. In this study, iron-doped g-C3 N4 (Fe-C3 N4 ) method was introduced to prepare a high active photocatalyst. The crystal structure and electronic structure of the Fe-C3 N4 were calculated by the First Principles. NO removal efficiency was used to evaluate the activity of Fe-C3 N4 . The results indicated that the NO removal efficiency was 75.43% when Fe-doped content was 1%. Ultraviolet–Visible (UV–Vis) and Photoluminescence (PL) spectra shows that the Fe doped changed the band structure of g-C3 N4, and reduced the band gap energy, which indicated that Fe-doped could improve the utilisation of visible light. X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) spectra shows that the Fe doped did not change the crystal structure of g-C3 N4 . The NO removal efficiency of three methods was tested. The results indicated that the dispersion spraying method had the best degradation efficiency of 35.8%.